Rancang Bangun Sistem Informasi Kepegawaian Berbasis Web : (Studi Kasus : Bum Desa Podho Joyo Sukorejo) - Moh. Adhim; Putri Aisyiyah Rakhma Devi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
BUM Desa Podho Joyo Sukorejo has an integrated information system in 1 website application, starting from HR, operations, and finance. However, the staffing information system is still less effective and efficient. The purpose of this research is to comprehensively describe the design of the staffing information system implemented at BUM Desa Podho Joyo Sukorejo. The solution that can be applied to overcome this problem is to develop a website-based staffing information system. The process of designing this system is done through direct observation method to BUM Desa Podho Joyo Sukorejo to collect accurate staffing data. The author chose to apply the waterfall method, a model in the System Life Development Cycle (SDLC) that involves system analysis, design, coding, and testing in sequence. The programming language used in this system is PHP, using Bootstrap as a web design library and MySQL as a database server. After performing a series of steps, including observation, design, and system development, it can be concluded that this system can assist employee staff in carrying out real-time recording of personal data, attendance, work history, and performance evaluation that can be accessed by related parties.